Teaching Psychology At Undergraduate Level: Rethinking What We Teach And How We Teach It - Sonja Goedeke (New Zealand Journal of Teachers' Work)
Traditionally undergraduate psychology has maintained an allegiance to a positivist scientist-practitioner model and has focussed on building a solid theoretical foundation. The development of skills and self-awareness has typically been the domain of postgraduate study. It is argued that in the process of trying to justify itself as a ‘science’, psychology has lost many of the aspects that first attracts people to its study: the desire for greater understanding of self, others and social phenomena. This article reflects on the experience of offering an undergraduate degree that integrates theory and a valuing of personal and vocational development. A less positivist-dominated formulation of the scientist-practitioner model may offer a constructive way in which to unite the ‘human’ and ‘scientific’ sides of psychology.